Supplier innovativeness, organizational learning styles and manufacturer performance: An empirical assessment - Azadegan, Arash; Dooley, Kevin J. (Journal of Operations Management, 2010)
AbstractSuppliers have become an increasingly important source of product and process innovation. While case studies have documented how supplier innovation can benefit a manufacturer, this relationship has not been empirically validated, nor have contingencies been explored. Using organizational learning theory we posit that the link between supplier innovativeness and manufacturer performance is moderated by the “fit” between the learning styles of the manufacturer and supplier. We empirically test our hypotheses using hierarchical linear modeling of survey responses from 148 manufacturers concerning 592 suppliers. Results indicate that supplier innovativeness has positive impacts on multiple dimensions of manufacturer performance. Results show that when the outsourced activity involves low levels of design responsibility by the supplier, it is more beneficial for the two partners to have contrasting learning styles. However, when the outsourced activity is design‐intensive, it is more beneficial to have a supplier with an explorative learning style.